“Nasi Sawo” as a Legitimacy of The Rejang Tribe Community's Traditional Marriage in The Urf Perspective - Suwarjin Suwarjin (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2020)
This study examines the tradition of